Ecological Vision and Human Conscience in Perumal Murgan’s Rising Heat (International Journal of Food and Nutritional Sciences, 2022)
Ecocriticism is the analysis of a literary work from the perspective of the natural world and societal environmental change. Ecocriticism holds that nature has a substantial influence on a text. It is the presentation and consideration of environmental challenges, cultural conflicts, and human attitudes toward nature. This paper deals with the Ecological Vision and Human Conscience of the novel Perumal Murgan’s Rising Heat. The author's dialect, which he utilised to explore Tamil culture and tradition, is also shown in the research. As an English translation of a Tamil book, the words from Tamil are used to highlight the true essence of the characters, forest, and community.